2017
DOI: 10.1007/s10903-017-0646-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physicians’ Role in Parental Decision to Vaccinate with HPV Vaccine: Learnings from a South Texas Hispanic Patient Population

Abstract: Hispanic populations have low HPV vaccination rates, although the vaccine is safe and efficacious. We surveyed a low-income Hispanic population to characterize knowledge gaps about the HPV vaccine and understand factors associated with the decision to vaccinate a child to determine how physicians can enhance vaccination rates. Surveys in English and Spanish were distributed to parents of children under age 18. Statistical analysis included logistic regression. Knowledge that the vaccine can prevent invasive ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Previous studies have found intention correlated with HPV vaccine initiation for adolescent girls [36,39,40]. However, a paucity of studies exist examining the association between parental intentions and vaccination outcomes among Hispanic adolescent females specifically, and few have examined psychosocial correlates of intention to vaccinate among Hispanic parents [41]. Our study contributes to the literature by describing the associations between IBM constructs and vaccination behaviors among this population to inform future intervention development.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have found intention correlated with HPV vaccine initiation for adolescent girls [36,39,40]. However, a paucity of studies exist examining the association between parental intentions and vaccination outcomes among Hispanic adolescent females specifically, and few have examined psychosocial correlates of intention to vaccinate among Hispanic parents [41]. Our study contributes to the literature by describing the associations between IBM constructs and vaccination behaviors among this population to inform future intervention development.…”
Section: Discussionmentioning
confidence: 85%
“…Research has shown that healthcare provider / physician recommendation and parents' trust in healthcare providers is positively associated with parents' uptake of the HPV vaccine. 20,21,25,26,33 Survey respondents reported higher vaccination rates when they were recommended to get the HPV vaccine for their child by their healthcare provider compared to those who did not receive recommendations. Previous research has shown that parents who vaccinate their children are more likely to remember and report higher quality recommendations from providers, i.e., providers recommending HPV as high importance for patients at ages 11-12.…”
Section: Reasons For Low Vaccination Ratesmentioning
confidence: 99%
“…11 In addition to parents, healthcare providers play a crucial role in ensuring its administration. [21][22][23][24][25][26][27][28] It is important for healthcare providers to bundle HPV vaccines with other required vaccines, such as tetanus-diphtheria-pertussis (Tdap) and meningococcal vaccine (MCV4, MenB). 29,30 They are encouraged to consistently and equally recommend HPV vaccination to parents of female and male children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may positively or negatively influence women’s screening participation decisions and decision-making around HPV vaccination [46]. For example, US studies consistently show that health professional recommendation is one of the strongest influences on parental decisions regarding HPV vaccination of their children [7,8]. However, in theoretically-robust research, we found that lack of HPV knowledge among PCPs was a key barrier to them performing cervical cancer prevention-related behaviours appropriately [2].…”
Section: Introductionmentioning
confidence: 99%